(untitled) (Eurasian Medical Research Periodical, 2022)
One hundred and seventy-six specimens (urine) from women anage range of 17–40 years were collected from October 2021 to April 2022 in sterilized containers from AL-KUT hospital. All isolates were identified according to their morphological characteristics Biochemical tests and Vitek 2 System were used to confirm the final diagnosing.Results were show 70 (77.77) E.coli isolates were obtained from 176 urine samples from women suffering from UTI symptoms,45(64%) being of Symptomatic Samples and 25(36%) of Asymptomatic Samples women, and 50(71.42) Pregnant and 20(28.57) nonpregnant,diabetes 27(3.85) and not present 43(61.5), were also detected from the obtained isolates. Susceptibility test was determined for all pathogenic E.coli isolates to 16 different antibiotics (Ampicillin, Piperacillin, Cefazolin, Cefoxitin, Ceftazidime, Ceftriaxone, Cefepime, Ertapenem, Imipenem, Amikacin, Gentamicin, Ciprofloxacin, Levofloxacin, Tigecycline,Nitrofurantoin, and Trimethoprim). The result showed that all pathogenic E.coli isolates had high resist (100%) to Ampicillin, Cefazolin, Ceftriaxone, Cefepime, Trimethoprim and Ceftazidime. 40% of isolates were resist to Cefoxitin, 15% of isolates were resist to Gentamicin, 66% of isolates were resist to Nitrofurantoin, while 100% of isolates were sensitive to Piperacillin, Ertapenem, Imipenem, Amikacin, Ciprofloxacin,Levofloxacin and Tigecycline.